Inventário do patrimônio arquitetônico do núcleo histórico da cidade de Santiago/RS - Flôres, Cáira Borondi (2016)
The preserved architecture allows a materialization of the places’ memory; it transmits the society events and creations to the future generations. The permanency of these buildings keeps alive the collective city memory. So, this research has as the mainly objective to inventory the buildings that are part of the city architectural history in Santiago, in the Vale do Jaguari, in the Midwest of Rio Grande do Sul. The selected goods are part of the original city history core, identified by this study and all of them respect the architectural, historical and artistic values. This is an applied and qualitative research, with the purpose to preserve the architectural patrimony; it’s descriptive when using the search for information and knowledge from the happenings and goods. It uses a historical method, because it investigates the buildings and their past processes; besides having a bibliography and documental approach, looking for searching concepts related to the patrimony’s memory preservation and the values as a classification method to the inventory. First, the historical core is demarcated, the place where the city formation began, identifying the buildings from the three first decades of the XX century with historical and architectural value and the ones that still remain their original characteristics. Searching for more representative, these buildings were selected by the ones that meet the requirement of having value or architectural, historical and artistic quality, this way, six buildings from the historical core stand out. As a final product, it is accomplished the goods inventory, that will serve as a base for the later preservation processes through the community and public power. Besides a catalog production of the inventoried buildings to contribute to the knowledge, that is a patrimony in the city and the beginning of the Santiago’s collective memory preservation.